A dor de um doce lar: narrativas da violência doméstica - Silva, Socorro Alves da (2010)
The study of domestic violence is an important theme that has been arousing interest in social and human sciences researchers. In order to contribute to a better knowledge of this subject, this research had as objective to comprehend the experience of women in domestic violence situation and the ways that these women subject this violence. It is a work that intended to put on the agenda the need of an organization with systematic services of global attention, considering the different requests regarding health, social and legal protection. The importance given to the problem is due to the increasing awareness of gender hierarchy and inequality, the recognition of women’s rights and the consistent evidences of the phenomenon’s great magnitude at a world level. The participants were women resident in the cities of Recife and Afogados da Ingazeira/PE – Sertão do Pajeú who usually seeks the services of Grupo Mulher Maravilha non-governmental organization. The instrument used to approach this phenomenon was semi-structured interviews which were performed individually. Collected data were grouped in thematic axis according to their nucleus of meanings for a better comprehension. The analyzed data shows the difficulty that women find in breaking up with the suffered violence by letting themselves to expose their situation through different reasons: the fear of their partner kills them and the possibility of their children see their father arrested; the credit given to the matrimony and family concept; the fact of they feel sorry for the partner to be an alcoholic or for he is unemployed ; and because they cannot find effective help from the organizations of woman’s defense. It is valuable to emphasize that this data corroborates with the idea that the roots of domestic violence against women are founded in a society that is based in a patriarchal system, fruit from the disparity between men and women of different races and social and cultural positions. Therefore, violence is observed as a complex matter as well as the politic solutions for its prevention and eradication and so requiring a wide comprehension of the problem. In the other hand, this research shows the importance of the clinic psychology in the break process of domestic violence contributing for a rescue of women’s self-esteem and autonomy in their attempt to interrupt the violence cycle and the matrimonial and domestic pacts which to they are submitted.